2007
DOI: 10.1002/jclp.20361
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar disorder: What can psychotherapists learn from the cognitive research?

Abstract: Randomized controlled trials of psychological treatment, principally cognitive therapy, for bipolar disorder have yielded inconsistent results. Given the status of this evidentiary base, we provide a more fine-grained analysis of the cognitive profiles associated with bipolar disorder to inform clinical practice. In this practice-friendly review, we consider evidence that both negative and positive cognitive styles are related to bipolar disorder. Cross-sectional and prospective evidence suggest that negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In addition, BD patients always exhibit poorer neuropsychological performance than UD [42], consistent with our finding that BD patients showed significantly lower score on the WAIS-Digit symbol relative to UD patients. Therefore, abnormal functional connectivity of cerebral cortex in BD but not UD might explain the clinical phenomenon that cognitive impairment are more severe in BD relative to UD [43]. The limbic region is a central part of the ‘‘emotional brain’’ circuitry responsible for the processing and regulation of emotion [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BD patients always exhibit poorer neuropsychological performance than UD [42], consistent with our finding that BD patients showed significantly lower score on the WAIS-Digit symbol relative to UD patients. Therefore, abnormal functional connectivity of cerebral cortex in BD but not UD might explain the clinical phenomenon that cognitive impairment are more severe in BD relative to UD [43]. The limbic region is a central part of the ‘‘emotional brain’’ circuitry responsible for the processing and regulation of emotion [14].…”
Section: Discussionmentioning
confidence: 99%
“…Hypomania is associated with unrealistically high goals and increasing overconfidence in one's abilities. People at-risk for the disorder may become more overconfident in the face of success than their peers, which suggests that an overly positive cognitive style may be a risk factor for hypomania—although no prospective studies have examined this hypothesis (Johnson & Tran, 2007). Escalating overconfidence may signal the onset of a hypomanic episode and set the occasion for impulsive behavior, which is a good reason for clinicians who treat bipolar disorder to attend to these types of thoughts.…”
Section: Overly Positive Thoughts In Adhd: What Do We Know?mentioning
confidence: 99%
“…We only used the total scores of the DAS-A-NL, as its subscales have not been validated in research. Still, Johnson and Tran (Johnson and Tran, 2007), and Lam and colleagues (Lam et al, 2004) suggested that patients with BD possibly have higher scores on the subscale goal attainment. Consequently, using total scores of the instrument may do no justice to this aspect of BD.…”
Section: Discussionmentioning
confidence: 99%